Post-warranty maintenance optimization for products with deterioration depending on aging and shock. Issue 6 (2nd November 2019) - Shang, Lijun; Cai, Zhiqiang; Chen, Hudong; Zhang, Shuai
ABSTRACT: Due to the non-substitutability of the product, the monopoly manufacturer designs warranty to reduce maximally warranty cost. Although the monopoly manufacturer maintains responsibly product reliability in warranty, the consumer still confronts a problem about how to sustain product reliability after the designed warranty expires. Goal of this paper is, from the consumer's perspective, to propose a reliability maintenance policy after expiry of the monopoly manufacturer's warranty. First, a renewable repair-limit pro-rata replacement warranty (RRLPRRW) policy is considered from viewpoint of the monopoly manufacturer and used as a quality guarantee of the product with the deterioration affected by internal aging and external shock. Second, depreciation cost is earlier considered in the process of modeling life cycle cost, which differs from the traditional works on the consumer's post-warranty reliability maintenance problem. Third, the consumer's discounted cost rate model considering depreciation cost is derived to achieve optimal maintenance policy. Finally, a numerical example is provided to illustrate our approach. It was found that the proposed maintenance policy is more effective and the depreciation cost considered in life cycle cost has significant effect on extension of the post-warranty period.